Potential Red Leaves Extract on Improving The Effectiveness of Antibiotic in Postpartum (Study Experiment of Perineum Wound Healing Process) - Rizkie Aulia Amini; Ari Suwondo; Ta'adi Ta'adi (Jurnal Kebidanan, 2022)
Background: Puerperal infection is caused by the entry of bacteria through uterine or perineal wounds. These bacteria can trigger proinflammatory cytokines. Excessive proinflammatory response results in tissue damage, septic shock to death. Among the non-pharmacological methods are extracts of red betel leaves which have phytochemical screening of flavonoids and tannins as antibacterial and antiseptic.Purposes: Knowing the potential of simplicia extract of red betel leaf on increasing the effectiveness of antibiotic in postpartum (study experiment of the process of healing of perineal wounds).Method: Quasi-experimental post-test only with control group design. Subjects were postpartum mothers with episiotomy perineal wounds that were sewn at Ummu Hani Purbalingga Mothers and Child Hospital using purposive sampling with a total of 38 respondents. The treatment group was given amoxicillin and red betel leaf simplicia extract, the control group was given amoxicillin and perineum wound care standard service. Provision of intervention carried out for 7 days, the measurement instrument for perineal wound healing is the REEDA score. Data analysis using independent t-test.Result: An independent test between the two groups found a mean difference in perineal wound healing p-value 0.0001. On intervention group the mean of perineal wound healing in day 5 and control group day 7.Conclusion: There is potential for simplicia red betel leaf extract to increase the effectiveness of antibiotic in postpartum.